CLINIC AND TREATMENT OF ACUTE AND RECURRENT HERPETIC STOMATITIS IN YOUNG PATIENTS - Burkhonova Zarafruz Qobilovna; Kaky Huda Abdul Salam Hekmat (Journals Park Publishing, 2022)
The lecture presents data on the etiopathogenesis, clinic, diagnosis and treatment of acute and recurrent herpetic stomatitis in children. Particular attention is paid to diagnostics and modern treatment protocols.
Keywords: herpetic stomatitis, children, etiology, pathogenesis, clinic, diagnosis, treatment. Herpes (from the Greek herpes - creeping) has been known for more than 2 thousand years. In total, about 80 representatives of the herpes virus have been discovered